USING MIN-MAX ANT ALGORITHM TO DETERMINE AIR ENEMY PLAN TO DESTROY ELEMENTS OF AIR DEFENSE SYSTEM - Taran І. А.; Starodubtsev S. О. (Honor and Law, 2019)
The paper proposed the method of using the multi-agent algorithm to determine air enemy plan to destroy elements of air defense system. Using this method we can determine means of air attack flight paths. There are the results of the calculations.